Autonomous Air Quality Measurement By Drone - Lázničková, Jana (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
In our project, we are interested air quality in region of Brno. We measure air quality with gas sensors attached on the drone. We record the results on a heat map. On this project, I work together with my friend Dominik Fuxa. He is in charge of communications and I am concerned with data acquisition and processing.
Keywords: Air quality; sensors; drone; heat map